Lineage B Genotype III of Dengue Virus Serotype 3 (DENV-3III_B) Is Responsible for Dengue Outbreak in Dire Dawa City, Ethiopia, 2023 - Abebe Aseffa Negeri; Dawit Hailu Alemayehu; Saro Abdella Abrahim; Tsigereda Kifle Wolde; Gutema Bulti Tura; Alemnesh Hailemariam Bedasso; Danile Tsega Geretsion; Ebise Abose Djirata; Eyilachew Zenebe Awule; Diana Rojas-Gallardo; Asefa Konde Korkiso; Kalkidan Melaku; et al. (Viruses)
The eastern parts of Ethiopia, including Dire Dawa City, have experienced annual dengue fever (DF) outbreaks since 2013, leading to significant healthcare and economic impacts. However, comprehensive evidence on the specific dengue virus (DENV) serotypes and genotypes involved remains limited. During the 2023 DF outbreak, the National Arbovirus Laboratory received seventy serum samples from suspected DF patients. Positive samples underwent sequencing of the CprM region of the DENV genome, and the obtained sequences were analyzed phylogenetically. Among the patients, 32 (45.7%) displayed early warning signs of severe dengue, and 13 were hospitalized, most showing symptoms indicative of severe dengue. Out of 67 adequate samples, 44 (65.6%) tested positive for DENV RNA by RT-PCR, and 17 successfully underwent CprM sequencing. All sequenced samples were identified as DENV-3, genotype III, major lineage B (DENV-3III_B), with two distinct minor lineages (DENV-3III_B.2 and DENV-3III_B.3). Phylogenetic analysis showed that these lineages were closely related to sequences from the Afar region, suggesting interconnected outbreaks with multiple co-circulating lineages. This study identifies DENV-3III_B as the cause of the 2023 DF outbreak in Dire Dawa City and highlights the need for enhanced viral genomic surveillance in Africa.